2008
DOI: 10.1002/msj.20017
|View full text |Cite
|
Sign up to set email alerts
|

A model for using community‐based participatory research to address the diabetes epidemic in east harlem

Abstract: Objective-Diabetes prevalence and mortality are increasing, with minority populations disproportionately affected. Despite evidence that weight loss due to improved nutrition and increased physical activity can prevent or control diabetes, there is often a disconnect between this evidence and individuals' lifestyles. Methods-EastHarlem is a predominantly African-American and Latino neighborhood that has the highest rates of diabetes prevalence and mortality in New York City. The East Harlem Diabetes Center of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 52 publications
0
49
0
Order By: Relevance
“…Hispanics were more likely to be in the younger age group where diabetes mellitus is less prevalent. This may explain in part why DM was less prevalent among this racial/ethnic group compared with non-Hispanic whites and non-Hispanic blacks [42][43][44]. This study showed African American with the highest prevalence of diabetes mellitus, indicative of racial/ethnic disparities in diabetes mellitus in this sample.…”
Section: Discussionmentioning
confidence: 60%
“…Hispanics were more likely to be in the younger age group where diabetes mellitus is less prevalent. This may explain in part why DM was less prevalent among this racial/ethnic group compared with non-Hispanic whites and non-Hispanic blacks [42][43][44]. This study showed African American with the highest prevalence of diabetes mellitus, indicative of racial/ethnic disparities in diabetes mellitus in this sample.…”
Section: Discussionmentioning
confidence: 60%
“…56 Creating a supportive environment is necessary to make consistent, healthier choices; however, the motivation to maintain such behavior may be affected by one's attitude. 57 Attitudes about health were measured at pre and post in this study but did …”
Section: Discussionmentioning
confidence: 99%
“…For example, air quality monitors, which initially yielded few findings, were relocated in response to community input, detecting grossly elevated particulate matter. This led to the removal of the diesel powered school buses from the area, and in the process highlighted the issue of environmental disparities and dumping [15,16].…”
Section: Rationale For Increasing the Number Of Investigators From Unmentioning
confidence: 99%